UNIVERSAL SERIAL BUS TECHNOLOGY (USB) 2.0 AND THE COMPARISON WITH FIREWIRE / ELECTRICS AND ELECTRONICS INSTITUTE ENGNEERS (IEEE) 1394 - Puri Setyawati; Fivtatianti H., SKom, MM Fivtatianti H., SKom, MM (Jurnal Sistem Komputer, 2006)
In line with current technological developments, particularly in the field of hardwarethat has made it easier for users to do something or work. With the discovery of thehardware used for data storage or files in very large quantities and high data transferspeed, then no longer need to use floppy disks or compact discs (CDs) used to storedata or files in very limited or small.At this writing, discussing about the speed of data transfer or file on Universal SerialBus (USB) 2.0 that can do the process of transferring achieve 480-Mbps, faster thanFirewire / Institute Electrics and Electronics Engineers (IEEE) in 1394 which has thespeed in transferring data or files reach 400 Mbps.Universal Serial Bus (USB) has a data transfer method, "Master-Slave" in whichcomputers have the authority to handle all the functions and set the data rate to / fromand between the peripherals used. While for Firewire (IEEE 1394) in data transferusing the "Peer to Peer" such as communication between the scanner and printer,where peripherals can overcome problems that occur on the bus and can determinewhich device can perform or control the data transfer.